Synthesizing habitat connectivity analyses of a globally important human‐dominated tiger‐conservation landscape. Issue 4 (20th April 2022) - Schoen, Jay M.; Neelakantan, Amrita; Cushman, Samuel A.; Dutta, Trishna; Habib, Bilal; Jhala, Yadvendradev V.; Mondal, Indranil; Ramakrishnan, Uma; Reddy, P. Anuradha; Saini, Swati; Sharma, Sandeep; Thatte, Prachi; et al.
Abstract: As ecological data and associated analyses become more widely available, synthesizing results for effective communication with stakeholders is essential. In the case of wildlife corridors, managers in human‐dominated landscapes need to identify both the locations of corridors and multiple stakeholders for effective oversight. We synthesized five independent studies of tiger ( Panthera tigris ) connectivity in central India, a global priority landscape for tiger conservation, to quantify agreement on landscape permeability for tiger movement and potential movement pathways. We used the latter analysis to identify connectivity areas on which studies agreed and stakeholders associated with these areas to determine relevant participants in corridor management. Three or more of the five studies' resistance layers agreed in 63% of the study area. Areas in which all studies agree on resistance were of primarily low (66%, e.g., forest) and high (24%, e.g., urban) resistance. Agreement was lower in intermediate resistance areas (e.g., agriculture). Despite these differences, the studies largely agreed on areas with high levels of potential movement: >40% of high average (top 20%) current‐flow pixels were also in the top 20% of current‐flow agreement pixels (measured by low variation), indicating consensus connectivity areas (CCAs) as conservation priorities. Roughly 70% of the CCAs fell within village administrative boundaries, and 100% overlapped forest department management boundaries, suggesting that people live and use forests within these priority areas. Over 16% of total CCAs' area was within 1 km of linear infrastructure (437 road, 170 railway, 179 transmission line, and 339 canal crossings; 105 mines within 1 km of CCAs). In 2019, 78% of forest land diversions for infrastructure and mining in Madhya Pradesh (which comprises most of the study region) took place in districts with CCAs. Acute competition for land in this landscape with globally important wildlife corridors calls for an effective comanagement strategy involving local communities, forest departments, and infrastructure planners. Resumen: Conforme los datos ecológicos y los análisis asociados están cada vez más disponibles, la síntesis de los resultados para la comunicación efectiva con los actores es esencial. En el caso de los corredores de fauna, los gestores en los paisajes dominados por humanos necesitan identificar tanto la ubicación de los corredores como a los múltiples actores para tener una vigilancia efectiva. Sintetizamos cinco estudios independientes sobre la conectividad de tigres ( Panthera tigris ) en el centro de la India, un paisaje de prioridad global para la conservación de esta especie, para cuantificar la armonía sobre la permeabilidad del paisaje para el movimiento de tigres y las vías potenciales de movimiento. Usamos el segundo análisis para identificar a los actores asociados con estas áreas y las áreas de conectividad en las que los estudios estaban de acuerdo para determinar a los participantes relevantes en la gestión de los corredores. Tres o más de las capas de resistencia de los cinco estudios estuvieron de acuerdo en un 63% del área de estudio. Las áreas en las que todos los estudios estuvieron de acuerdo sobre la resistencia fueron principalmente las de resistencia baja (66%, p. ej.: bosques) y alta (24%, p. ej.: áreas urbanas). La armonía de acuerdos fue más baja en las áreas de resistencia intermedia (p. ej.: paisajes agrícolas). A pesar de estas diferencias, los estudios tuvieron una armonía generalizada en las áreas con niveles altos de movimiento potencial: >40% de los pixeles de flujo continuo de promedio alto (20%) estuvieron también en el 20% de los pixeles armónicos de flujo continuo (medidos por la baja variación), lo que indica que las áreas de conectividad unánime (ACUs) son prioridades de conservación. Aproximadamente el 70% de las ACUs se ubicaron dentro de los límites administrativos de las aldeas, y el 100% se traslapó con los límites de gestión del departamento de bosques, lo que sugiere que las personas viven y usan los bosques dentro de estas áreas prioritarias. Más del 16% del área total de las ACUs se ubicó a un kilómetro de la infraestructura lineal (437 cruces de carreteras, 170 de vías férreas, 179 de líneas de transmisión y 339 cruces de canales; 105 minas a un kilómetro de las ACUs). En 2019, el 78% de las desviaciones del suelo forestal para la infraestructura y la minería en Madhya Pradesh (que conforma la mayoría de la región de estudio) ocurrió en distritos con ACUs. La feroz competencia por tierras en este paisaje con corredores de fauna de importancia mundial exige una estrategia de comanejo efectivo que involucre a las comunidades locales, los departamentos de bosques y a los planeadores de infraestructura. 摘要: 一个全球重要的人类主导的虎保护景观中生境连接度的综合分析 随着生态学数据和相关分析越来越普遍, 对结果进行综合分析以便与利益相关者有效沟通也变得十分重要。就野生动物廊道而言, 人类主导景观中的管理者需要确定廊道的位置和多方利益相关者, 以进行有效监督。我们综合了对印度中部——一个全球虎( Panthera tigris )保护优先景观中的虎种群连接度的5项独立研究, 确定了对老虎移动的景观渗透性和潜在移动路径的共识。我们还利用潜在移动路径的分析确定了研究中一致的连通区域以及这些区域的利益相关者, 以确定廊道管理中相关的参与者。63%的研究区域在5项研究的至少3项中被认为是阻力层。所有研究一致得到的阻力区域主要是低阻力(66%, 如森林)和高阻力(24%, 如城市)地区, 而中等阻力(如农业)的地区一致性较低。尽管存在以上差异, 但这些研究得到的潜在移动水平高的地区基本一致:超过40%的高平均(前20%)电流像元同时也是前20%的一致电流像元(用低变异衡量), 表明一致连接区(CCAs)是保护的重点。大约70%的CCA位于村庄行政边界内, 且全部与林业部门的管理边界重叠, 这表明人们在这些保护优先区域内生活并利用森林。超过16%的CCA总面积在线性基础设施的1公里范围内(437条公路、170条铁路、179条输电线路和339个运河交叉口;还有105个矿场在CCA的1公里范围内)。2019年, 中央邦(包括了大部分研究区域)78%被改用于基础设施和采矿的林地都位于有CCA的地区。在这种具有全球重要性的野生动物廊道景观中存在着对土地的激烈竞争, 这要求人们采取有效的共同管理战略, 让当地社区、林业部门和基础设施规划者共同参与管理。【翻译:胡怡思;审校:聂永刚】